Presence Application on Nagari Devices Using Android-Based Qr Code: Aplikasi Presensi Perangkat Nagari Menggunakan Qr Code Berbasis Android - Revo Abdi Sabda; Yusran Yusran; Dwi Winarti (International Journal of Technology Vocational Education and Training, 2022)
Applications that are growing rapidly have provided various benefits in various agencies. The office of the Mayor of Nagari Koto Gadang is a government agency whose attendance system for Nagari devices is still done manually using a note. In this study, researchers designed an attendance application using a QR Code which was implemented at the Office of the Mayor of Nagari Koto Gadang utilizing a manual presence system towards a digital system. This application is built with a high level of mobility that utilizes a smartphone device as a media presence. The development method used in the Nagari device presence system uses the Waterfall Model, the design uses UML. The application functions as a QR Code. With this application, the Nagari device presence process is carried out using a smartphone device as a medium. This makes the attendance process easier by using the presence application using an Android-based QR Code. In its implementation, the application will also use Kodular as a function to make scans on smartphone devices.